Identificación de endoparásitos en aves Anseriformes en parques recreacionales de la ciudad de Loja - Celi Lojan, Juan Carlos (2021)
Anseriformes birds are definitive host of a variety of parasites, but there is limited information about endoparasites of urban free-ranging Anseriformes in Ecuador. The objective of this study was to identify the gastrointestinal parasites in free-ranging Anseriformes that inhabit three recreational parks (Jipiro, Daniel Alvarez Burneo and Zamora Huayco) in the city of Loja, Ecuador. From November 2019 to February 2020, 111 fresh fecal samples of ducks (54 Cairina moschata; 23 Anas p latyrhynchos domesticus), geese (19 Anser anser; 10 Anser cygnoides) and swans (2 Cygnus olor; 3 Cygnus atratus) were collected and analyzed by the sedimentation and Mini-FLOTAC flotation technique. A general prevalence of gastrointestinal parasitosis was 87.39% (97/111). In ducks, endoparasites included: Ascaridia spp (30.6%, n=00), Capillaria spp (60.5%, n=00), Heterakis spp (1.3%, n=00), Estrongylido (42.9%, n=00), coccidian oocysts (17.4%, n=00), amoeba ocysts (94.1%, n=00), trematode (26.1%, n=00) and pentastomid eggs (11.8%, n=00). In geese, Ascaridia spp (23.1%, n=00), Capillaria spp (29.2%, n=00), Estrongylido (53.8%, n=00), amoeba ocysts (100%, n=00), trematode (16.7%, n=00) and pentastomid eggs (33.3%, n=00). In swans, Estrongylido eggs (20%, n=00), amoebae ocysts (100%, n=00), trematode eggs (50%, n=00). The prevalence of parasites in birds was statistically different according to their body mass index (BMI) and the most frequently parasitized birds showed low-medium BMI index. Variables such as sex, location, bird did not show relationship to-parasitism frequency and intensity. Key words: Endoparasites; Anseriformes; Loja; Park